2010
DOI: 10.1111/j.1750-3639.2009.00284.x
|View full text |Cite
|
Sign up to set email alerts
|

TDP‐43 Redistribution is an Early Event in Sporadic Amyotrophic Lateral Sclerosis

Abstract: Amyotrophic lateral sclerosis (ALS) is a neurodegenerative disorder consisting of progressive loss of motor neurons. TDP-43 has been identified as a component of ubiquitinimmunoreactive inclusions of motor neurons in ALS. We focused on the diffuse cytoplasmic TDP-43 immunoreactivity in ALS neurons, and quantitatively assessed it in comparison with skein/round TDP-43 and ubiquitin immunostaining in motor neurons of 30 sporadic ALS cases. The percentage of spinal motor neurons with cytoplasmic TDP-43 immunoreact… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
125
0
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 125 publications
(143 citation statements)
references
References 43 publications
(76 reference statements)
12
125
0
1
Order By: Relevance
“…This redistribution of TDP-43 to the cytoplasm has been suggested to represent a landmark feature of the onset and progression of ALS/FTLD [23, 43], and in cell culture the disrupted trafficking of TDP-43 is a precursor to the formation of cytoplasmic TDP-43 inclusions [66]. Previously, Sato et al, [54] have reported the cytoplasmic mislocalisation of TDP-43 in response to neuronal stress in a mouse ligation model.…”
Section: Discussionmentioning
confidence: 97%
“…This redistribution of TDP-43 to the cytoplasm has been suggested to represent a landmark feature of the onset and progression of ALS/FTLD [23, 43], and in cell culture the disrupted trafficking of TDP-43 is a precursor to the formation of cytoplasmic TDP-43 inclusions [66]. Previously, Sato et al, [54] have reported the cytoplasmic mislocalisation of TDP-43 in response to neuronal stress in a mouse ligation model.…”
Section: Discussionmentioning
confidence: 97%
“…The mechanisms by which mutations in TARDBP cause neurodegeneration are unclear. Pathological assembly is associated with a marked reduction in nuclear TDP-43 staining and the cytoplasmic accumulation of TDP-43 is believed to be an early event (Giordana et al 2010). A combination of loss of function and gain of toxic function mechanisms may be at play.…”
Section: Mutations In Tardbpmentioning
confidence: 99%
“…In disease conditions, affected neurons typically lose nuclear TDP-43 staining, possibly before the formation of intracellular aggregates (21). In addition, TDP-43 seems to be ubiquitinylated, phosphorylated, and fragmented in pathological conditions (3).…”
mentioning
confidence: 99%